Vključevanje menedžerjev strateških poslovnih enot v odločanje o strategiji korporativne znamke - Riel, C. B. M. van (Teorija in praksa, 2007)
This article examines the issue of a relation between corporate brand and strategic unit brands in an organisation. The author presents a model, the so called SIDEC-model that can be used for internal decision making about the pros and cons of the use of uniform corporate brand. SIDEC stands for Strategy, Internal organization, Driving forces, Environment and Corporate branding strategy. Although a strong corporate brand can have added value for operating businesses in a conglomerate, the author argues that the introduction of a corporate umbrella does not necessarily mean that a uniform corporate branding strategy is the best solution. It would be advisable to organizations with complex organizational structures and large differences in the nature of the product/market combinations to develop their corporate branding strategy in a balanced manner.
Keywords: Corporations; Korporacije; Management; Upravljanje; strategija